Humor Maintenance and Translation Techniques in Cunk on Earth - In the Beginnings's Indonesian Subtitles - Salwa Caesar Ramadhanty Supratman; Issy Yuliasri (Universitas Islam Negeri Palopo, 2025)
This study (2023–2024) investigates humor translation challenges in audiovisual media, analyzing Indonesian subtitles of the British mockumentary Cunk on Earth (2022), a satirical show hosted by Philomena Cunk that parodies documentaries with absurd, deadpan comedy. Focusing on 128 humorous utterances (yielding 228 technique instances), the research applies Molina and Albir’s (2002) translation framework to identify strategies that preserve comedic effect amid cultural- linguistic gaps. A mixed-method approach combined qualitative analysis with audience evaluations: three native English speakers validated humor segments, while 15 Indonesian participants rated translation effectiveness on a three-point scale (entirely, partially, or lost). Findings revealed 12 techniques, with Literal Translation (24.78%), Linguistic Compression (16.37%), and Modulation (15.04%) most frequent. Surprisingly, Literal Translation succeeded most often (19.56% of fully preserved humor), while Adaptation and Compensation underperformed. Overall, 53.91% of translations retained the humor fully, underscoring the efficacy of specific techniques for mockumentary-style satire. The study highlights the importance of flexible, audience-tailored strategies in subtitling deadpan humor and provides empirical insights to audiovisual translation research, particularly for understudied genres such as mockumentaries. Practical implications for subtitling practice and training are discussed.